P570 Safety and Effectiveness of Tofacitinib in Ulcerative Colitis: Real-world Data from TOFA-UC, a SN-IBD Study. (30th January 2023) - Macaluso, F S; D'Antonio, E; Fries, W; Viola, A; Ksissa, O; Cappello, M; Muscarella, S; Belluardo, N; Giangreco, E; Mocciaro, F; Di Mitri, R; Ferracane, C; et al.
Abstract: Background: Real-world evidence is necessary to determine the safety and effectiveness of tofacitinib (TOFA) for the treatment of ulcerative colitis (UC) in clinical practice. Methods: TOFA-UC is a multicenter observational study performed among the Sicilian Network for Inflammatory Bowel Disease (SN-IBD) on a prospectively maintained database. All consecutive patients with UC starting TOFA from its introduction in Sicily (June 2021) to June 2022 (12 months) were enrolled. The primary outcome was the assessment of safety, in terms of rate of adverse events (AEs). Secondary outcomes included the rates of clinical response, steroid-free clinical remission (based on partial Mayo score) and C-Reactive Protein (CRP) normalization after 8 weeks and at the end of follow-up, the rate of loss of response, and treatment persistence. Results: 111 patients were included (mean follow-up: 31.5 ± 15.2 weeks). Only 8 patients (7.2%) were naïve to biologics, while most had previous failures to one (27.0%), two (26.1%), three (32.4%), or four (7.2%) biologics. Nineteen adverse events were reported (17.1%; incidence rate: 28.6 per 100 patient-year), including 11 cases of hypercholesterolemia, 3 infections (no cases of herpes zoster reactivation), nausea in two patients, paresthesia in one case, one colorectal cancer and one pulmonary embolism. At week 8, the rates of clinical response, steroid free clinical remission, and CRP normalization were 74.8%, 45.0%, and 56.9%, respectively, and 68.5%, 51.4%, and 65.2%, respectively, at the end of follow-up. Eighteen patients experienced a loss of response after successful induction (21.7%; incidence rate: 33.2 per 100 patient-year). The dose was increased to 10 mg bid in 15 patients, and 7 of them recaptured the response. A total of 26 patients (23.4%) discontinued TOFA over time, of whom 3 due to AEs. At multiple model regression analysis, being former smoker (hazard ratio=4.03; 95% CI=1.36-10.25; p=0.015) was the only variable associated with higher risk of treatment discontinuation. No significant differences in all outcomes of effectiveness were detected when the subgroup of patients naïve to biologics or with only one previous line of biologic therapy was compared with those with at least two previous lines of biologics. Conclusion: TOFA is safe and effective in patients with UC, including those with multiple previous failures to biological therapies.